Training of HOTS-Based Teaching Factory to Improve Teachers’ Competencies at SMK Muhammadiyah 6 Jakarta - Wahjusaputri, Sintha; Bunyamin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
This training aims at developing teachers' professionalisms andcompetencies that consist of analyzing, evaluating, creativity,and being able to conclude or solving problems at SMKMuhammadiyah 6, Jakarta. The training activities wereconducted from 10 to 12 February 2020 at SMKMuhammadiyah 6 Jakarta. The number of participants whoparticipated in the training was 17 people. The training useslecture, discussion, demonstration, and practice methods. Afterthe training, the participants practiced teaching factory topicsbased on HOTS and assisted by the PKM Team. The trainingresulted that the participants were satisfied that they showed thepresence of enthusiasts at each training meeting. Participantspresented a very well assessment of the attitude of activeness,cooperation, and responsibility towards mastering thedevelopment of HOTS-based teaching factories. Thesupporting factors for the PKM activities are (1) the availabilityof the team resources, (2) the enthusiasm of the participants,and (3) the support of the principal.